Performance of the fertility and prolificacy at birth in the current populations of three rabbit breeds in Artemisa, Cuba - García, D.; García, Yoleisy; Ponce de león, Raquel; Ginorio, Odalys (Cuban Journal of Agricultural Science, 2020)
In order to study the performance of fertility and prolificacy traits at birth (total born and live born), a total of 14 659 records of mating and 8 296 kindlings of the current rabbit populations of California, Chinchilla and New Zealand breeds were used between 2014 and 2017, belonging to a genetic unit. A mixed generalized linear model was used, which considered the fixed effects of breed, month, year and the interactions breed x month and breed x year, in addition to the random effect of the reproducers in its different mating or kindlings. It was found that all sources of variation considered in the model influenced on the analyzed traits, except the interaction of breed per month of mating in fertility, so the studied traits vary depending on the interaction between breeds and environmental conditions (month and year). The highest fertility occurred in the mating of April, March, May and July, and the lowest in January and August. California showed stability over time and remained the most fertile, when there were differences between breeds in the same year. There were divergences between breeds in the kindlings of February, June, September, October, November and December, with superiority of New Zealand, while Chinchilla had a worse performance for 70 % of those months. New Zealand remained the best in three years, with more than 5.6 total born and live born. This breed is ratified as the most promising for reproductive indicators that determine the rabbit productivity. Key words: reproduction, breeds, rabbits, productivity.